The Influence of variation the blade distance against the cocofibers and cocopeat percentage of the coconut fruit from Jambi Area - Emmistasega Subama; . Sepriyanto (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2019)
The influence of variationthe blade distance against the coco fiber and coco peat percentage of the coconut fruit from Jambi area has been done. The study aims to know the percentage of cocofiber and cocopeat produced based on the influence of variation the blade distance of decomposition machine starting from 5 cm, 10 cm and 15 cm. Each round speed will operate for 2 minutes with 500 grams of raw material and use 10 decomposing blades. The results show that (1) distance of blade provides an influence on the value of the cocofiber and cocopeat produced (2) on the distance between the blade 5 cm obtained cocofiber as much as 30% and 62% of cocopeat raw materials. On the distance between the blade 10 cm obtained as much as 34% and cocofiber cocopeat 58% of raw materials, on the distance between the blade 15 cm obtained as many as 32% and cocofiber cocopeat 60% of the raw material (3) maximum of cocopeat cocofiber results on 10 cm distance between the blade.